1978
DOI: 10.1099/00221287-108-1-17
|View full text |Cite
|
Sign up to set email alerts
|

The Chemotactic Response of Plasmodia of the Myxomycete Physarum polycephalum to Sugars and Related Compounds

Abstract: A new technique, the double strip method, for studying the chemotaxis of myxomycete plasmodia is described. Physarum polycephalum was attracted by the aldohexoses D-glucose, D-galactose and D-mannose and their derivatives 2-deoxy-~-glucose and maltose, thresholds ranging from 0.25 mM (D-glucose) to 5 mM (D-mannose). These sugars competed with each other, a uniform background of one of them inhibiting taxis to the others. Other attractants were N-acetyl-D-glucosamine and mannitol, with thresholds at 1 mM, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 10 publications
2
46
0
Order By: Relevance
“…The set-up (Fig. 3) consisted of a Petri dish with an acetate U-shaped trap placed between the plasmodium and a well in the agar containing food: an attractive 2% (wt/vol) glucose solution, the "goal" (16)(17)(18). The diffusing glucose solution produced an attraction gradient through the agar, drawing the plasmodium toward the glucose source and into the U-shaped trap.…”
Section: Resultsmentioning
confidence: 99%
“…The set-up (Fig. 3) consisted of a Petri dish with an acetate U-shaped trap placed between the plasmodium and a well in the agar containing food: an attractive 2% (wt/vol) glucose solution, the "goal" (16)(17)(18). The diffusing glucose solution produced an attraction gradient through the agar, drawing the plasmodium toward the glucose source and into the U-shaped trap.…”
Section: Resultsmentioning
confidence: 99%
“…A second consequence of high nutrient concentrations was that the higher the concentration of carbohydrate in the medium, the higher was the incidence of mortality. This may be related to the sensitivity of slime molds to high osmotic pressure (11,30,31). The osmotic effects of high sugar concentrations have been suggested to cause both reduced migration rate (31, 32) and negative chemotaxis (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that P. polycephalum increases allocation toward exploratory growth when its current food resource is diluted (22). On substrates with higher nutrient concentrations, the plasmodia in the present study grew more compactly, with slime molds on high-protein diets producing a veinless structure, indicating that media able to support rapid growth depress migration, allowing the organism to remain at a site until nutrients are exhausted (11,23).This result has strong parallels with observations in other distributed systems, such as bacterial and fungal colonies, in which the overall pattern of growth is influenced by varying the concentration of nutrient (20,24). The ratio of protein and carbohydrate in the diet also had a strong influence on migration distance.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Here we designed a protocol to investigate habituation phenomena in slime moulds using chemotaxis as the behavioural response under scrutiny. Chemotaxis is the directed motion of an organism towards favourable chemicals (attractants) and away from unfavourable ones (repellents) [19,20]. To test whether slime moulds are capable of habituation, individuals were repeatedly exposed to quinine or caffeine, known repellents for P. Polycephalum [21,22] and their behavioural responses were recorded.…”
Section: Introductionmentioning
confidence: 99%